An Overview of Cognitive Reserve in Aging Based on Keyword Network Analysis - Jihyun Kim PhD, RN; Mi So Kim PhD, RN (SAGE Publishing, 2022)
Many studies have reported that Cognitive reserve is a critical mechanism affecting cognitive statuses, such as dementia. The purposes of this study were to identify the knowledge structure and the research trend on cognitive reserve by conducting keyword analysis on research papers ranging from the earliest to the most recent studies done on the topic and to suggest directions for future research. The Web of Science (WOS) database was used to search for articles on cognitive reserve in aging from 2001 to 2020. NetMiner version 4 (cyram, KOREA), a social network analysis program, was used for keyword network analysis. Data analysis showed keywords that could be categorized as cognitive reserve related keywords (cognitive reserve related concepts, cognitive reserve related factor, cognitive reserve diagnosis and measurement, cognitive reserve outcomes) and cognitive reserve research keywords (research subject/disease, research method, intervention, research field). Through trend analysis, we found that various keywords appeared, indicating that the research has gradually developed conceptually and methodically. Based on these findings, future CR studies require the development of multimodal interface-based tools by applying modern digital technology that can be used to more accurately diagnose and monitor CR; remotely, in real time. In addition, to improve CR, it is suggested that the development of cognitive stimulation interventions utilizing VR which fuses AI based interaction technology with the subjects. Finally, CR could develop further through a cooperation of multidisciplinary professionals such as psychology, medicine and nursing.